1998
DOI: 10.1080/026990598122142
|View full text |Cite
|
Sign up to set email alerts
|

Performance of healthy adults versus individuals with brain injuries on the supplemental measures of the WAIS-R NI

Abstract: The Wechsler Adult Intelligence Scale-Revised as a Neuropsychological Instrument (WAIS-R NI) provides methods to uniformly interpret atypical responses or response patterns. To date, little research has examined the primary population for which the supplemental measures of the WAIS-R NI were intended. The purpose of the present study was to compare the performance of individuals with brain injuries versus healthy adults on the supplemental measures of the WAIS-R NI. Forty-nine healthy adults and 45 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Brain Damage. Mercer et al (1998) found that brain injury affected all supplemental measures on the WAIS-R NI (as a neuropsychological instrument). In particular, strong effects were noted for the scales of Digit Symbol (raw score), Digit Symbol Copy (raw score), Free Recall Digit Symbol, Spatial Span Backward, and Sentence Arrangement.…”
Section: Clinical Conditionsmentioning
confidence: 97%
“…Brain Damage. Mercer et al (1998) found that brain injury affected all supplemental measures on the WAIS-R NI (as a neuropsychological instrument). In particular, strong effects were noted for the scales of Digit Symbol (raw score), Digit Symbol Copy (raw score), Free Recall Digit Symbol, Spatial Span Backward, and Sentence Arrangement.…”
Section: Clinical Conditionsmentioning
confidence: 97%